2005
DOI: 10.1001/jama.294.3.334
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and Risk of Congestive Heart Failure

Abstract: Insulin resistance predicted CHF incidence independently of established risk factors including diabetes in our large community-based sample of elderly men. The previously described association between obesity and subsequent CHF may be mediated largely by insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
294
1
14

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 516 publications
(321 citation statements)
references
References 37 publications
12
294
1
14
Order By: Relevance
“…Adiposity is associated with increased risk of hypertension, 2 insulin resistance, 54 diabetes mellitus, 55 and dyslipidemia, 56 all of which increase the risk of myocardial infarction 57 and may thereby increase the risk of heart failure. 9,34,58 However, the exploratory analysis with and without adjustment for incident myocardial infarction suggested only small differences with such an adjustment, suggesting that a relatively small proportion of heart failure cases might be explained by this mechanistic pathway. Hypertension and diabetes mellitus also strongly increase the risk of heart failure independently of other risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Adiposity is associated with increased risk of hypertension, 2 insulin resistance, 54 diabetes mellitus, 55 and dyslipidemia, 56 all of which increase the risk of myocardial infarction 57 and may thereby increase the risk of heart failure. 9,34,58 However, the exploratory analysis with and without adjustment for incident myocardial infarction suggested only small differences with such an adjustment, suggesting that a relatively small proportion of heart failure cases might be explained by this mechanistic pathway. Hypertension and diabetes mellitus also strongly increase the risk of heart failure independently of other risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the Uppsala study, insulin sensitivity, but not anthropometric indexes of obesity, was independently predictive of HF risk. 99 In a cohort study from Greece, individuals with normal BMI and metabolic syndrome were at substantially higher risk of HF at 6 years compared with obese individuals without metabolic syndrome. 198 Analyses from MESA (Multi-Ethnic Study of Atherosclerosis) suggest that inflammation may potentiate the link between obesity and the risk of developing HF.…”
Section: Other Medicationsmentioning
confidence: 99%
“…18,19 Studies have also demonstrated that milder elevations in glucose and abnormalities in insulin resistance, even in the absence of overt diabetes mellitus, are associated with an increased risk for HF. 99,100 In individuals without known diabetes mellitus or HF at baseline in the ARIC study (Atherosclerosis Risk in Communities), the risk of incident HF was higher in individuals with hemoglobin A1c (HbA1c) of 6.0% to 6.4% (HR,1.40; 95% CI, 1.09-1.79) and HbA1c of 5.5% to 6.0% (HR,1.16; 95% CI, 0.98-1.37) compared with those with an HbA1c of 5.0% to 5.4% 100 ( Table 5). The mechanisms contributing to the greater degree of HF in individuals with diabetes mellitus are likely multifactorial and include the commonly shared HF risk factors of hypertension, coronary artery disease, renal 104 Between 1995 and 1999 in Olmsted County, Minnesota, the prevalence of diabetes mellitus in patients with incident HF was 25%.…”
Section: Association Of Diabetes Mellitus With the Development Of Incmentioning
confidence: 99%
“…Similar data were obtained from a Finnish study, showing a greater risk of HF in overweight and obese subjects than that in normal-weight participants . However, while some authors attribute these correlations to the downstream development of metabolic risk factors such as inflammation, insulin resistance or type 2 diabetes mellitus (Ingelsson et al 2005, Bahrami et al 2008, Voulgari et al 2011, the data from other studies report that obesity directly correlates with the risk of HF, independent of other metabolic risk factors (Morkedal et al 2014). Paradoxically, once HF has been established, obesity confers survival benefits (Oreopoulos et al 2008, Shah et al 2014.…”
Section: Obesity As a Risk Factor For Heart Failurementioning
confidence: 99%